Efficient protocol for genetic transformation and shoot regeneration of turmeric (Curcuma longa L.) via particle bombardment - Shirgurkar, M. V.; Naik, V. B.; von Arnold, S.; Nadgauda, R. S.; Clapham, D. H. (Plant Cell Reports, 2006)

Studies of antimicrobial activity of turmeric (Curcuma Longa L.) leaves and rhizomes collected during plant growth phases - Shirgurkar, M. V.; Thengane, Shubhada Ratnakar (Research Journal of Biotechnology, 2010)
Turmeric is the processed underground rhizome used as spice, herbal medicines, dying agent and cosmetics. The leaves and rhizomes of this plant were collected at periodic intervals. These samples were air dried, powdered and extracted with MeOH and EtOH. Antibacterial activity of these extracts was determined against three different index microbes, gram-positive cocci, gram-negative rod and cocci using well diffusion method with appropriate controls. Antimicrobial activity of the 4-month-old leaves was found to be the maximum while that of mature and fresh rhizomes was the maximum against both gram-positive and Gram-negative bacteria.
Keywords: antibacterial activity; Curcuma longa; Leaf extract; Minimum inhibitory concentration; rhizome extract

Efficient shoots regeneration and genetic transformation of bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Gupta, Neha; Ruby; Shirgurkar, M. V.; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2015)
Bacopa monniera is an important source of metabolites with pharmaceutical value. It has been regarded as a valuable medicinal plant and its entire commercial requirement is met from wild natural population. Recently, metabolic engineering has emerged as an important solution for sustained supply of assured and quality raw material for the production of active principles. Present report describes efficient in vitro multiplication and transformation method for geneticmanipulation of this species. MS medium supplemented with 2 mgl(-1) BA and 0.2 mgl(-1) IAA was found optimum for maximum shoot regeneration (98.33 %) from in vitro leaves with 2-3 longitudinal cuts. Agrobacterium tumefaciens-mediated transformation method was used for generating transgenic B. monniera plants. Putative transformants were confirmed by GUS assay and PCR based confirmation of hptII gene. DNA blot analysis showed single copy insertion of transgene cassette. An average of 87.5 % of the regenerated shoots were found PCR positive for hptII gene and GUS activity was detected in leaves of transgenic shoots at a frequency of 82.5 % The efficient multiple shoots regeneration system described herein may help in mass production of B. monniera plant. Also, the high frequency transformation protocol described here can be used for genetic engineering of B. monniera for enhancement of its pharmaceutically important metabolites.